Load Balancing Algorithms For Distributed Service Architectures - Chen, Li Choo (2003)
This project investigates the impact of diffrent load balancing algorithms on the network performance in the distributed object-oriented service architectures. Besides two new load-balancing algorithms have been proposed in this projects. They are the Random Sender Initiated Algorithm and the Node Status Algorithm.